Intracellular trafficking of influenza virus M1 protein at late stages of the infectious cycle - Drake, Aymé (2021)
Influenza A –the main responsible for seasonal "flu"– is an RNA virus containing a single-stranded and segmented RNA of negative polarity and belongs to the Orthomyxoviridae family. In humans, influenza A mainly affects the upper respiratory tract causing considerable morbidity and mortality with local epidemic outbreaks and occasionally pandemic worldwide spread. The World Health Organization (WHO) estimates that seasonal circulating influenza results in about 3–5 million cases of severe illness and about 250,000 to 500,000 deaths. The replication cycle of influenza A fully depends on the host cell metabolic pathways. Thus, the translation of the viral mRNAs is divided between cytosolic (PB1, PB2, PA, NP, NS1, NS2, and M1) and endoplasmic reticulum (ER)-associated ribosomes (HA, NA and M2). It is clear that M1, the main viral capsid protein, plays a critical role during the influenza infectious cycle by controlling the entry, replication, and nuclear export of a complete set of viral genomes and proteins (vRNPs). However, little is known about the role of M1 during vRNPs trafficking in route to host the plasma membrane where the viral particles are being assembled. Focusing on the late stages of influenza A infectious cycle, our results indicate that M1 associates with acidic compartments at the last stages, mainly colocalizing with typical late endosomal/lysosomal markers such as Rab7a, Rab9a, CD63, LAMP1, and the LysoTracker probe. Interestingly, bafilomycin A1, an inhibitor of the vesicular proton pump, induces specific re-location of viral M1 from late membranous compartments to the cytosol, suggesting that a functional organelle is required for M1 proper cellular targeting. Therefore, we speculate that late endosomes/lysosomes might act as pre-assembling platforms where not only M1 but other structural influenza proteins such as HA, NA or M2 and vRNPs transiently converge and eventually interact one with another in order to form maturing intermediate viral particles just before to reach the host cell surface.